Studi Formulasi Sabun Padat Santan dengan Variasi Konsentrasi Minyak Kelapa dan Minyak Sawit - wuryandari, wahyu; Pamella, Melani Safira (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Solid soap is a cleansing product derived from the saponification of fatty acids and bases. The fatty acids used were coconut oil and palm oil. Coconut oil and palm oil contained lauric acid, palmitic acid, and oleic acid, each of which functioned to produce lather, hardness, and moisturizing properties in the soap. Coconut milk contained oleic acid, stearate, and linoleate, serving as moisturizers. Coconut milk could be used as a substitute for water to dissolve NaOH. This study aimed to ascertain the physical and chemical quality of solid coconut milk soap with variations in concentrations of coconut oil and palm oil. The study was conducted as an experimental research. Solid coconut milk soap was manufactured using the cold process method. The soap was formulated into three different recipes. The results of physical and chemical quality tests of the three formulations showed water content testing yielded 7.88% (formula 1), 7.95% (formula 2), and 9.63% (formula 3). Foam height testing resulted in 11.6 cm (formula 1), 11.3 cm (formula 2), and 11.3 cm (formula 3). pH testing showed values of 9.63 (formula 1), 9.76 (formula 2), and 9.73 (formula 3). Free alkali testing indicated 0.089% (formula 1), 0.094% (formula 2), and 0.084% (formula 3). The conclusion drawn from this research is that solid coconut milk soap with variations in concentrations of coconut oil and palm oil meets the 2021 Indonesian National Standards for organoleptic properties, water content, pH, and free alkali content.